Peningkatan Hasil Belajar Siswa pada Mata Pelajaran Matematika melalui Metode Pemberian Tugas di Kelas II MIS Muhammadiyah Sibatua - Sukmawati Sukmawati; Nurain Nurain; Muh Fahrul Nur; Tarman A. Arif; Idawati Fadollah; Suleha Zubair (Departement of Mathematics Education, 2023)
The practice of strengthening the teaching profession (P2K) is one of the academic requirements within the University of Muhammadiyah Makassar, especially in the department of primary school teacher education, which is oriented towards application and at the same time training for the knowledge gained. In the practice of strengthening the teaching profession, students conduct a class action research. This study aims to find out that mathematics learning outcomes can be improved through the method of giving assignments in class II, such as Muhammadiyah Sibatua. Whether or not there is a difference in student learning outcomes between the assignment method and the absence of the use of the assignment method in a lesson, which one has the greatest influence on the learning outcomes of class II students, e.g. Muhammadiyah Sibatua. The form of action taken in solving problems that exist in Classroom Action Research (CAR) is by learning using the assignment method. So it is hoped that it can improve the learning outcomes of class II students, such as Muhammadiyah Makassar. The method used in this research is descriptive with a classroom action research approach (CAR). While the data collection techniques and tools in the form of observation or observation is a technique or method of collecting data by observing ongoing activities. There are several things that must be considered in carrying out observations, including; Pay attention to the focal point of the study, determine the criteria to be observed. In carrying out observations there are several main steps that must be taken, including; planning meetings, class observations, feedback discussions. The purpose of each method of giving assignments in learning is very influential in every learning process because it will determine which direction the learning will be successful or not in accordance with the learning objectives to be achieved.